Alteration to hippocampal volume and shape confined to cannabis dependence: a multi‐site study. (18th July 2018) - Chye, Yann; Lorenzetti, Valentina; Suo, Chao; Batalla, Albert; Cousijn, Janna; Goudriaan, Anna E.; Jenkinson, Mark; Martin‐Santos, Rocio; Whittle, Sarah; Yücel, Murat; Solowij, Nadia
Abstract: Cannabis use is highly prevalent and often considered to be relatively harmless. Nonetheless, a subset of regular cannabis users may develop dependence, experiencing poorer quality of life and greater mental health problems relative to non‐dependent users. The neuroanatomy characterizing cannabis use versus dependence is poorly understood. We aimed to delineate the contributing role of cannabis use and dependence on morphology of the hippocampus, one of the most consistently altered brain regions in cannabis users, in a large multi‐site dataset aggregated across four research sites. We compared hippocampal volume and vertex‐level hippocampal shape differences (1) between 121 non‐using controls and 140 cannabis users; (2) between 106 controls, 50 non‐dependent users and 70 dependent users; and (3) between a subset of 41 controls, 41 non‐dependent users and 41 dependent users, matched on sample characteristics and cannabis use pattern (onset age and dosage). Cannabis users did not differ from controls in hippocampal volume or shape. However, cannabis‐dependent users had significantly smaller right and left hippocampi relative to controls and non‐dependent users, irrespective of cannabis dosage. Shape analysis indicated localized deflations in the superior‐medial body of the hippocampus. Our findings support neuroscientific theories postulating dependence‐specific neuroadaptations in cannabis users. Future efforts should uncover the neurobiological risk and liabilities separating dependent and non‐dependent use of cannabis. Abstract : In a large multisite dataset of 261 subjects, reduced hippocampal volume was found in cannabis‐dependent users relative to non‐dependent users and controls, irrespective of cannabis dosage. However, non‐dependent users did not differ from controls in hippocampal volume. Shape analysis indicated localized deflations in the superior‐medial body of the hippocampus, driving the findings in dependent users.